Catalysis Sans Catalyst Loss: The Origins of Prolonged Stability of Graphene–Metal–Graphene Sandwich Architecture for Oxygen Reduction Reactions - Abdelhafiz, Ali; Choi, Ji Il; Zhao, Bote; Cho, Jinwon; Ding, Yong; Soule, Luke; Jang, Seung Soon; Liu, Meilin; Alamgir, Faisal M. (Advanced science, 2023)
Over the past decades, the design of active catalysts has been the subject of intense research efforts. However, there has been significantly less deliberate emphasis on rationally designing a catalyst system with a prolonged stability. A major obstacle comes from the ambiguity behind how catalyst degrades. Several degradation mechanisms are proposed in literature,   but with a lack of systematic studies, the causal relations between degradation and those proposed mechanisms remain ambiguous. Here, a systematic study of a catalyst system comprising of small particles and single atoms of Pt sandwiched between graphene layers, GR/Pt/GR, is studied to  unravel the degradation mechanism of the studied electrocatalyst for oxygen reduction reaction(ORR). Catalyst suffers from atomic dissolution under ORR harsh acidic and oxidizing operation voltages. Single atoms trapped in point defects within the top graphene layer on their way hopping through toward the surface of GR/Pt/GR architecture. Trapping mechanism renders individual Pt atoms as single atom catalyst sites catalyzing ORR for thousands of cycles before washed away in the electrolyte. The GR/Pt/GR catalysts also compare favorably to state‐of‐the‐art commercial Pt/C catalysts and demonstrates a rational design of a hybrid nanoarchitecture with a prolonged stability for thousands of operation cycles. Catalyst protection through sandwiching between two graphene sheets enhances stability without compromising the activity to catalyze oxygen reduction reaction in acidic medium. Spectroscopic and computational analyses reveal the catalyst degradation mechanism. Under oxygen reduction reaction (ORR) conditions, evolution of point defects in graphene top layers provides a tortuous path for single atoms to reach the catalyst surface to catalyze ORR.